2022
DOI: 10.3390/su141811116
|View full text |Cite
|
Sign up to set email alerts
|

Study on Relationship between Environmental Regulation and Green Total Factor Productivity from the Perspective of FDI—Evidence from China

Abstract: The existing literature has paid less attention to the key role of FDI in the realization of Porter’s hypothesis. Based on China’s provincial panel data from 2007 to 2020, this paper uses the SBM function and the Luenberger productivity index to measure the green total factor productivity (GTFP) of China’s provinces while considering energy consumption and undesired output. Using FDI as the mediating variable and threshold variable, this paper studies the relationship between environmental regulation (ENV), FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The third is the non-linear hypothesis, which states that environmental regulation has asymmetric effects on green total-factor productivity. A large number of scholars have argued that environmental regulations have a U-shaped effect on green total-factor productivity [ 19 , 20 , 21 , 22 ] or an inverted U-shaped effect [ 23 , 24 , 25 , 26 , 27 ]. However, Brännlund found environmental regulation had no significant impact on the productivity of manufacturing enterprises in Sweden [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The third is the non-linear hypothesis, which states that environmental regulation has asymmetric effects on green total-factor productivity. A large number of scholars have argued that environmental regulations have a U-shaped effect on green total-factor productivity [ 19 , 20 , 21 , 22 ] or an inverted U-shaped effect [ 23 , 24 , 25 , 26 , 27 ]. However, Brännlund found environmental regulation had no significant impact on the productivity of manufacturing enterprises in Sweden [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been shown that heterogeneous environmental regulations can significantly contribute to the green transformation of manufacturing enterprises. Moreover, the existing literature provide a more comprehensive empirical examination of the factors influencing heterogeneous environmental regulations but lack comprehensiveness [ [121] , [122] , [123] ]. Therefore, this study further discusses the heterogeneous impacts of environmental policy uncertainty, property rights, and regions on the relationship between environmental regulations and the green transformation of manufacturing enterprises.…”
Section: Further Analysismentioning
confidence: 99%
“…However, the effect on the enhancement of managers' green cognitive ability is also relatively weak due to the low level of regulation. Moreover, the existing literature provide a more comprehensive empirical examination of the factors in uencing heterogeneous environmental regulations but lack comprehensiveness [121][122][123]. Therefore, this study further discusses the heterogeneous impacts of environmental policy uncertainty, property rights, and regions on the relationship between environmental regulations and the green transformation of manufacturing enterprises.…”
Section: Mechanism Analysismentioning
confidence: 99%